Task-based language teaching in the Indonesian language classroom for foreign learners - Pastini, Ni Wayan; Hardina, Hardina (Yayasan Mitra Persada Nusantara, 2025)
This article explores the implementation and pedagogical implications of Task-Based Language Teaching (TBLT) in the context of Bahasa Indonesia instruction for foreign learners. As global interest in learning Bahasa Indonesia continues to grow, particularly through programs such as BIPA (Bahasa Indonesia untuk Penutur Asing), there is a pressing need to adopt instructional methods that not only promote communicative competence but also foster learner autonomy and engagement. TBLT has gained prominence in second and foreign language education due to its emphasis on authentic language use, real-world tasks, and learner-centered approaches. This study investigates the effectiveness of TBLT in enhancing the linguistic and pragmatic abilities of foreign learners in Indonesian language classrooms through a review of relevant literature and selected case studies from BIPA programs. The analysis reveals that TBLT facilitates more meaningful learning experiences by aligning classroom activities with learners' communicative needs. It encourages interaction, negotiation of meaning, and contextual language practice, which are essential for language acquisition. However, the study also identifies challenges, such as designing culturally appropriate tasks, assessing learner performance, and training instructors in task-based methodology. Recommendations are offered for curriculum development, teacher training, and future research to support the effective integration of TBLT in BIPA curricula. This article contributes to the growing body of research on innovative language teaching methodologies in Southeast Asia and highlights the potential of TBLT to transform Indonesian language education for foreign learners into a more dynamic, responsive, and outcomes-driven process.